Determination of catechins in green tea leaves by HPLC compared to spectrophotometry - Oleksandr Yu. Maslov (National University of Pharmacy (Kharkiv, Ukraine), 2021)
Aim. To study the qualitative composition, the quantitative content of catechins in green tea leaves and compare the data obtained with those evaluated by spectrophotometry. Materials and methods. Green tea leaves used for the analysis were collected in Anhui Province, China. The extract for the HPLC analysis was obtained by the maceration method with 60% ethanol twice in the raw material/extractant ratio of 1:20. In the case of the spectrophotometric analysis, green tea leaves were extracted with 70 % ethanol twice by the maceration method in the raw material/extractant ratio of 1:20. The analysis of the extract from green tea leaves was performed by high performance liquid chromatography using a Prominence LC-20 Shimadzu chromatographic system (Japan) with a SPD-20AV spectrophotometric detector, an Agilent Technologies Microsorb-MV-150 column (reversed phase, C18 modified silica gel, length – 150 mm, diameter – 4.6 mm, particles size – 5 μm). Substances in the extract were identified by comparing the retention time and the spectral characteristics of the test substances with the same characteristics of the reference standards. Spectrophotometric measurements were carried out using a UV-1000 single beam spectrophotometer (China) with the pair of S90-309Q quartz square cells. Results and discussion. Using high performance liquid chromatography 5 catechins were identified. Among them epigallocatechin-3-O-gallate (10.85%) predominated, while catechin (0.61%) had the lowest concentration. The total amount of catechins in green tea leaves was 30.56 and 24.79% by HPLC and spectrophotometry, respectively. The F- and t-tests showed that there was no significant difference between the results of HPLC and spectrophotometry. Conclusions. The qualitative composition and the quantitative content of catechins have been determined in the extract from green tea leaves by high performance liquid chromatography and spectrophotometry. Both HPLC and spectrophotometric methods can be used to determine the total catechin content in green tea leaves. The high content of catechins makes the extract promising for further study and creation of new herbal medicinal products and dietary supplements. The results obtained will be used for standardization of green tea leaves and for future pharmacological research of its extract.